An advanced SDOF model for steel members subject to explosion loading material rate sensitivity - Chinien, Viken (Steel Construction Institute, 2002)
This technical note describes an extension to a sophisticated single-degree-of-freedom (SDOF) model for steel members subject to explosion loading.
Keywords: Blast effect.; Steel, Structural.; Structural analysis (Engineering); elektronické knihy; electronic books